2013
DOI: 10.1002/mma.2803
|View full text |Cite
|
Sign up to set email alerts
|

Existence, blow-up, and exponential decay estimates for a system of nonlinear wave equations with nonlinear boundary conditions

Abstract: This paper is devoted to the study of a system of nonlinear equations with nonlinear boundary conditions. First, on the basis of the Faedo–Galerkin method and standard arguments of density corresponding to the regularity of initial conditions, we establish two local existence theorems of weak solutions. Next, we prove that any weak solutions with negative initial energy will blow up in finite time. Finally, the exponential decay property of the global solution via the construction of a suitable Lyapunov functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…By employing the nonlinear semigroups and the theory of monotone operators, the well-posedness of (1.2) is moderately investigated. An important result obtained in [7] and further in [14] is that every weak solution blows up in finite time, provided the initial energy is negative and the sources are more dominant than the damping involved in the system. In [3,4], Cavalcanti et al studied the existence of global solutions, and showed the relation between the asymptotic behavior of the energy and the degenerate system of wave equations with boundary conditions of memory type.…”
Section: Vo Anh Khoa Le Thi Phuong Ngoc and Nguyen Thanh Longmentioning
confidence: 99%
See 3 more Smart Citations
“…By employing the nonlinear semigroups and the theory of monotone operators, the well-posedness of (1.2) is moderately investigated. An important result obtained in [7] and further in [14] is that every weak solution blows up in finite time, provided the initial energy is negative and the sources are more dominant than the damping involved in the system. In [3,4], Cavalcanti et al studied the existence of global solutions, and showed the relation between the asymptotic behavior of the energy and the degenerate system of wave equations with boundary conditions of memory type.…”
Section: Vo Anh Khoa Le Thi Phuong Ngoc and Nguyen Thanh Longmentioning
confidence: 99%
“…Accounting for the Kirchhoff-Love plate theory in shear deformations, the system (1.1) is closely related to the Reissner-Mindlin plate equations (see [9]), structured by three coupled wave and wave-like equations involving the influence of nonlinear damping and source terms. Mathematically, systems of wave equations have been extensively studied by many authors, see [1,4,7,14,15,16] and references therein where the existence, regularity and the asymptotic behavior of solutions are investigated.…”
Section: Vo Anh Khoa Le Thi Phuong Ngoc and Nguyen Thanh Longmentioning
confidence: 99%
See 2 more Smart Citations
“…Below we present an example such that the functions f 1 , f 2 , G satisfy the assumptions (H 3 ) , (H 4 ), respectively. In this example, f 1 , f 2 are more general than the functions given in [19,21].…”
mentioning
confidence: 99%